Challenges and a response strategy for the development of nursing in China: a descriptive and quantitative analysis. Issue 1 (28th February 2013) - Wang, Yingqiang; Wei, Shiyou; Li, Youping; Deng, Shaolin; Luo, Qianqian; Li, Yan
Abstract Objective To assess the challenges to and provide a response strategy for the development of nursing and make suggestions for promoting the nursing discipline, platform, and talent teams based on current best available evidence. Methods We searched CNKI(China National Knowledge Infrastructure), VIP information(Chinese Scientific Journals database), CBM(Chinese Biomedical Literature database), and Web sites of the World Health Organization, International Council of Nurses, World Bank, the Ministry of Health and the Ministry of Education of China, and relevant schools in China. Data analyses were performed using SPSS 13.0. Results We identified 886 nursing schools in China in 2012. Results showed that 38, 212 nursing students were enrolled in universities or independent colleges and 130, 837 nursing student were enrolled in colleges or senior vocational schools. The doctor‐to‐nurse ratio was 1:0.9 in 2010. The actual demand for doctors was 2.6 million, whereas the nursing shortage was approximately 346, 000. Nurses aged ≤35 years accounted for 50% of the total. A total of 64% to 69% of nurses had primary professional titles; fewer than 2.5% of those had advanced titles. The training costs for one doctor or one nurse in China was only two‐fifths that in India and one‐fifth to one‐fourth that in sub‐Saharan Africa. To date, only 30.1% of disaster nursing studies in China provided research data; 30.6% were related to clinical experience and 38.3% were reviews. Conclusions Education and health systems need to be extensively reformed. It is necessary to train nursing students with core competencies using transformative learning. It is necessary to update textbooks and teaching methods, and funding should be appropriately increased. Nursing should co‐operate with other disciplines, and apply evidence‐based nursing methods to improve the quality of healthcare services and patient satisfaction.